2023
DOI: 10.15252/emmm.202217177
|View full text |Cite
|
Sign up to set email alerts
|

Bi‐allelic pathogenic variants in PABPC1L cause oocyte maturation arrest and female infertility

Abstract: Oocyte maturation arrest is one of the important causes of female infertility, but the genetic factors remain largely unknown. PABPC1L, a predominant poly(A)-binding protein in Xenopus, mouse, and human oocytes and early embryos prior to zygotic genome activation, plays a key role in translational activation of maternal mRNAs. Here, we identified compound heterozygous and homozygous variants in PABPC1L that are responsible for female infertility mainly characterized by oocyte maturation arrest in five individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…Female mice with Pabpc1l knockout have been demonstrated to be infertile with complete arrest in MI and could not generate mature oocytes for fertilization 33,34 . However, recently, Wang et al reported that bi‐allelic pathogenic variants in PABPC1L caused human female infertility characterized by various phenotypes including oocyte maturation arrested at the GV or MI stage, fertilization failure, and early embryonic development arrest 36 . Wang et al also generated knock in (KI) mice model corresponding to the variants in their patients, and interestingly, the female KI mice ovulated mature MII oocytes after superovulation and the infertility was attributed to early embryonic arrest after IVF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Female mice with Pabpc1l knockout have been demonstrated to be infertile with complete arrest in MI and could not generate mature oocytes for fertilization 33,34 . However, recently, Wang et al reported that bi‐allelic pathogenic variants in PABPC1L caused human female infertility characterized by various phenotypes including oocyte maturation arrested at the GV or MI stage, fertilization failure, and early embryonic development arrest 36 . Wang et al also generated knock in (KI) mice model corresponding to the variants in their patients, and interestingly, the female KI mice ovulated mature MII oocytes after superovulation and the infertility was attributed to early embryonic arrest after IVF.…”
Section: Discussionmentioning
confidence: 99%
“…Female mice with global deletion of Pabpc1l were infertile and generated no mature oocytes or embryos in vivo or in vitro due to impaired translational activation, chromatin configuration, and transcriptional silencing 33–35 . However, to date, only one study has reported that variants in PABPC1L caused human female infertility 36 . More PABPC1L mutations need to be uncovered to confirm the relationship between PABPC1L and human fertility.…”
Section: Introductionmentioning
confidence: 99%
“…The latter is particularly important for potential infertility alleles impacting gamete development or function because it is not yet feasible to accurately recapitulate gametogenesis in vitro . In this issue of EMBO Molecular Medicine , Wang et al ( 2023 ) present a comprehensive pipeline to identify and interpret pathogenic variants from infertility patients, using a degree of rigor that is exceptional for the reproductive genetics field.…”
mentioning
confidence: 99%
“…In their study, Wang et al ( 2023 ) aimed to identify the genetic causes of OMA, a disease that results in female infertility and is a major contributor to in vitro fertilization failure. OMA can manifest at different stages of meiosis, and a few genes functioning in diverse processes such as recombination, spindle assembly, zona pellucida formation, and translational repression have been linked to OMA in women (Huang et al , 2014 ; Chen et al , 2017 ; Liu et al , 2017 ; Maddirevula et al , 2017 ; Dai et al , 2019 ; Zhang et al , 2020 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation